2020
DOI: 10.1136/bmjoq-2019-000735
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an interdisciplinary malnutrition quality improvement project at a large metropolitan hospital

Abstract: As many as 50% of hospitalised patients are estimated to be malnourished or at risk of malnutrition on hospital admission, but this condition often goes unrecognised, undiagnosed and untreated. Malnutrition is associated with an elevated need for continued medical interventions, higher costs of care and increased patient safety risks. Tampa General Hospital (TGH), a large teaching hospital in the southeastern USA, initiated a project to improve the quality of patient care at its institution. They did this firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 24 publications
3
23
0
1
Order By: Relevance
“…Third, the percentage of patients with diagnosed malnutrition receiving an RDN‐developed nutrition care plan increased in 2 (urology and general medicine) of 5 targeted services, indicating that patients who needed nutrition care were more likely to receive it. This contributes to a growing body of evidence on nutrition‐focused QI projects being effective in addressing patient nutrition care 3–6,8,11 . Fourth, the high percentage of oncology patients identified as being at malnutrition risk or malnourished supports previous work demonstrating that oncology patient populations have important nutrition care needs 12,13 …”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Third, the percentage of patients with diagnosed malnutrition receiving an RDN‐developed nutrition care plan increased in 2 (urology and general medicine) of 5 targeted services, indicating that patients who needed nutrition care were more likely to receive it. This contributes to a growing body of evidence on nutrition‐focused QI projects being effective in addressing patient nutrition care 3–6,8,11 . Fourth, the high percentage of oncology patients identified as being at malnutrition risk or malnourished supports previous work demonstrating that oncology patient populations have important nutrition care needs 12,13 …”
Section: Discussionsupporting
confidence: 53%
“…A number of US hospitals have demonstrated that nutrition‐focused quality improvement (QI) programs or initiatives can be effectively implemented to improve patient care while improving the health and economic outcomes of at‐risk/malnourished patients 4–6 . Effective implementation of standardized metrics is key to measuring progress and assessing the impact of initiatives on both processes and patient outcomes 5–7 .…”
Section: Introductionmentioning
confidence: 99%
“…One U.S. teaching hospital has reported using elements of the MQii Toolkit to measure and improve quality, and as a part of their initiative, they began providing free, early immunonutrition supplements and nutrition education to high-risk patients with colorectal cancer during preadmission testing. Overall, they reported significant reductions in length of stay (LOS) (from 8 to 6 days, p < 0.01) and infection rates (from 14% to 9%, p < 0.01) for patients who were malnourished or at risk of malnutrition, although they did not report specific results for the cancer subpopulation [50]. Similar to this institution, cancer care teams could readily adapt MQii tools and processes for use in oncology clinics to provide more inclusive care.…”
Section: Discussionmentioning
confidence: 97%
“…Other researchers have observed an association between malnutrition and HAIs [ 15 , 16 , 17 ]. Importantly, the improvement of nutritional care in malnourished in-patients or in-patients at risk of malnutrition resulted in a 35.7% reduction in HAI rate [ 18 ].…”
Section: Introductionmentioning
confidence: 99%